Association between the use of electronic cigarettes and myocardial infarction in U.S. adults - María José Farfán Bajaña; Juan Carlos Zevallos; Ivan Chérrez-Ojeda; Geovanny Alvarado; Tiffany Green; Betty Kirimi; Daniel Jaramillo; Miguel Felix; Emanuel Vanegas; Alejandra Farfan; Manuel Cadena-Vargas; Daniel Simancas-Racines; et al. (BMC, 2024)
Abstract Background Compared with conventional cigarettes, electronic cigarettes are less harmful in some studies. However, recent research may indicate the opposite. This study aimed to determine whether e-cigarette use is related to myocardial health in adults in the U.S. Methods This study used data from the 2020 Behavioral Risk Factor Surveillance System (BRFSS), a cross-sectional survey of adult US residents aged 18 years or older. We examined whether e-cigarette use was related to myocardial infarction byapplying a logistic regression model to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Results The final analytical sample included 198,530 adults in the U.S. Logistic regression indicated that U.S. adults who reported being former and some days of e-cigarette use had 23% and 52% greater odds of ever having an MI, respectively, than did those who reported never using e-cigarettes (OR = 1.23, 95% CI 1.08-1.40, p = 0.001; OR = 1.52, 95% CI 1.10-2.09, p = 0.010). Conclusions The results suggest that former and someday users of e-cigarettes probably have increased odds of myocardial infarction in adults in the U.S. Further research is needed, including long-term follow-up studies on e-cigarettes, since it is still unknown whether they should be discouraged.